Analysis of the Foundations of Curriculum Development Management in Islamic Boarding Schools - Ziyadul Ifdhal Ghazali; Jalaluddin Madani; Mahsusil Arofi (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2024)
Nowadays, the implementation of learning in schools, madrasah, or Islamic boarding schools is always related to the curriculum as a reference in the implementation of learning. A curriculum is a set of subjects provided by educational institutions to students that are tailored to educational goals, community needs, and the development of the times. The curriculum by some education experts is analogous to a building built on the main foundations. This research aims to reveal and explain the foundations of curriculum formulation and development in Islamic boarding schools. The research method used in this study is a literature study by collecting several related literature in the form of books, journals, articles, documents and so on as primary data. The results of the study show that there are at least five main foundations in the formulation and development of the curriculum in Islamic boarding schools, namely the spiritual-religious foundation, philosophical foundation, psychological foundation, socio-cultural foundation, and the foundation of science and technology development